Democratic Republic of the Congo : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix investigates the sources of growth in the Democratic Republic of the Congo (DRC) and evaluates the relative importance of productivity growth and factor accumulation. The analysis is extended to the key sectors of the economy: agriculture, mining, and transport. The paper assesses the DRC's medium-term growth prospects and compares them with both the post-conflict growth experience to date and the growth objectives of the Poverty Reduction and Growth Facility-supported program. The paper also suggests a simple, yet powerful, methodology for projecting the real GDP growth rate.